2011
DOI: 10.5935/1678-9741.20120007
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos resultados imediatos da cirurgia de revascularização do miocárdio com e sem circulação extracorpórea

Abstract: Objective: The objective of this study is to compare the immediate results of patients undergoing on-pump versus off-pump coronary artery bypass graft (CABG) surgery.Methods: From January 2007 to January 2009, 177 patients underwent CABG. Of these, 92 underwent off-pump CABG and 85 on-pump CABG. We evaluated the demographics, preoperative risk factors, preoperative functional class, and risk assessment by the EuroSCORE. A comparison between both groups regarding the postoperative evolution was carried out as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
2
5
0
2
Order By: Relevance
“…Coronary artery bypass grafting (CABG) aims to increase the life expectancy of patients with improved quality of life, relief of myocardial ischemia symptoms, and improvement of ventricular function [2] , but there are still high rates of complications [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery bypass grafting (CABG) aims to increase the life expectancy of patients with improved quality of life, relief of myocardial ischemia symptoms, and improvement of ventricular function [2] , but there are still high rates of complications [3] .…”
Section: Introductionmentioning
confidence: 99%
“…All patients in our study underwent surgery with cardiopulmonary bypass. Various data available in the literature indicate advantage of CABG technique without cardiopulmonary bypass in selected [ 25 ] cases, however, although controversial in some points the "ROOBY" study showed no difference between the results of neuropsychological outcomes between CABG with and without CPB [ 26 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Neste contexto, para tratamento da doença arterial coronariana (DAC), a cirurgia de revascularização do miocárdio (CRM) é uma opção com indicações precisas de médio a longo prazo e com bons resultados. 1,3 A CRM tem permitido, durante as últimas décadas, que os pacientes com DAC aumentem a sobrevida, reduzam os sintomas e melhorem a qualidade de vida. No entanto, esse tipo de cirurgia está associado a um índice de morbidade em torno de 15%, incluindo infecção, acidente vascular encefálico (AVE), hemorragia, síndrome do baixo débito, complicações pulmonares e fibrilação atrial.…”
Section: Introductionunclassified